The role of organizational harmony in enhancing strategic response: An analytical study of the opinions of a sample of members of the visitor cities affiliated with the Holy Shrine of Imam Hussein / Holy Karbala - هديل محمد علي عبد الهادي; سحر عباس حسين; حسام حسين شياع (Iraqi Journal for Administrative Sciences, 2024)
The research aims to test the relationship and impact of organizational harmony on strategic response. By analyzing the relationship between the dimensions of each of them, the importance of the research lies in its treatment of two important variables in the organizational environment, The research was based on a major problem represented by the weakness of the strategic response in the Iraqi service organizations, the study sample. The research included several questions revolving around the nature of the relationship between its variables. (370) questionnaires were distributed to a number of workers in the visitor cities affiliated with the Al-Abbas’s (p) Holy Shrine. (321) questionnaires were retrieved, while (305) questionnaires were valid for statistical analysis. The sample’s answers were analyzed using a number of statistical programs. The theoretical results showed the existence of a knowledge gap to explain the relationship between research variables in organizations in general and in the study sample in particular. The applied results also showed a positive and significant effect between the research variables